2020
DOI: 10.1093/tropej/fmaa013
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Severity Score with Regard to Birthweight during the Early Days of Life for Predicting Pulmonary Hypertension in Preterm Infants

Abstract: Objective The respiratory severity score (RSS) has been demonstrated to be associated with the oxygenation index in intubated newborn infants. We aimed to evaluate the usefulness of RSS with regard to birthweight (BW) in preterm infants for predicting an association with future pulmonary hypertension (PH). Methods Preterm infants with <30 weeks’ gestation and <1250 g BW were reviewed and grouped into two (PH vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…[ 18 , 19 ] Furthermore, several studies have shown its predictive value for mortality, BPD, and other short-term morbidities. [ 20 , 21 , 23 ] Mhanna et al . [ 22 ] investigated the utility of RSS for predicting extubation readiness in very-low-birth-weight infants and found that it was the only statistically significant risk factor for extubation failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 , 19 ] Furthermore, several studies have shown its predictive value for mortality, BPD, and other short-term morbidities. [ 20 , 21 , 23 ] Mhanna et al . [ 22 ] investigated the utility of RSS for predicting extubation readiness in very-low-birth-weight infants and found that it was the only statistically significant risk factor for extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] A study in which the RSS was analyzed by weight (RSS/kg) found that RSS/kg was more useful for predicting the development of pulmonary hypertension than the RSS. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the same MAP value should lead to various effect sizes in different lungs. For example, Seo YM et al (18) pointed out the fact that a MAP of 10 cmH 2 O would lead to differential effects in the lungs of an infant with a birth weight of 500 g and in the lungs of an infant with a birth weight of 1000 g and calculated RSS as well as RSS/kg in the first 5 days of life in their study that intended to investigate the relationship between the development of pulmonary hypertension and RSS. They also found elevated RSS only on days 2 and 4, while RSS/kg was increased throughout the whole 5-day period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on RSS have established the ease of use, predictive value for morbidity and mortality, as well as utility in the early phases of life, for this scoring tool. However, most of these studies followed a singlecenter approach, involving patients managed within that center following labor (15,16,18,26,32). In this regard, our study differs from these previous investigations, as it was a multi-center study and included referrals from other centers within the first 6 hours of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation